1991
DOI: 10.1007/bf01456792
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient adolescent and latency-age children's perspectives on the curative factors in group psychotherapy

Abstract: Thirty-three adolescent and 11 child psychiatric inpatients were administered a downward revision of Yalom's (1970) With epidemiological studies of childhood psychopathology indicating prevalence rates from a minimum of 6% to a maximum of 20%, the need for effective treatments for disorders of childhood and adolescence is clear (Graham, 1979;Miller et al., 1974;Rutter et al., 1970).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
5

Year Published

1994
1994
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
5
0
5
Order By: Relevance
“…Only factors about which the raters agreed were used; factors for which there was no agreement were not used in further analyses. Some therapeutic factors [2, 5, 8] were mentioned by almost every participant while others occurred almost never [3, 9, 11]. Because the aim of this study was to identify factors that differentiated between successful and unsuccessful treatments, factors that were not expected to differentiate because of low or high frequency were excluded from further analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only factors about which the raters agreed were used; factors for which there was no agreement were not used in further analyses. Some therapeutic factors [2, 5, 8] were mentioned by almost every participant while others occurred almost never [3, 9, 11]. Because the aim of this study was to identify factors that differentiated between successful and unsuccessful treatments, factors that were not expected to differentiate because of low or high frequency were excluded from further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Although as effective as individual therapy [7], it is argued that group psychotherapy, with its focus on peer relationships and identity formation, is preferable for adolescents [8]. To provide an understanding of clients’ perceptions of the effectiveness of group psychotherapy in general, Corsini and Rosenberg [9] and later on Yalom [10] devised the concept of therapeutic factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that participants' selfreported hopelessness was significantly related to self-reported sexual victimization suggests that psychotherapy may be beneficial in alleviating the deleterious effects of some forms of sexual aggression, as the instillation of hope is considered a fundamental ingredient of most forms of psychotherapy (Frank, 1974;Lantz & Pegram, 1989;Yalom, 1985). In particular, group approaches are considered to be particularly effective at fostering hope (Chase, 1991;Couch & Childers, 1987;Goldberg, McNiel, & Binder, 1988;Yalom, 1985). Thus, women who feel hopeless following sexual victimization may benefit from participating in groups designed to provide psychotherapy, selfhelp, andlor mutual support (Canetto, 1995).…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…There is a growing body of research that finds group psychotherapy effective for this population: Lockwood (1981), Berkovitz and Sugar (1975), Peck and Bellsmith (1954), and Schaefer, Johnson, and Wherry (1982). A unique study by Chase (1991) identifies important curative factors in adolescent and child group psychotherapy. He found that both adolescent and child group members valued hope, cohesiveness, and universality.…”
mentioning
confidence: 99%